Studi Komparatif Kemampuan Mahārah Qirā’ah Siswa Pesantren Salafi dan Khalafi di Aceh Barat, Indonesia - Dara Mubshirah (DAYAH: Journal of Islamic Education, 2022)
Arabic is one of the materials studied in modern (khalafi) and traditional (salafi) Islamic Boarding Schools (Pesantren). Reading comprehension ability (Mahārah Qira’āh) is one of the crucial skills in learning Arabic. This study aimed to determine the extent of the differences in the qirā’ah ability in Pesantren Khalafi and Salafi in West Aceh. This study uses a comparative method. To collect the data, the researcher employed tests on 50 students of Pesantren Salafi and 50 students Pesantren Khalafi. Whereas to analyze the data researcher employed the Mann Witney statistical test with a = 0.05. The results of this study showed that there was a difference between the Mahārah Qirā’ah ability of Students in Pesantren Khalafi and Salafi with the statistical value of reading lined texts (p-value (0.011) <α (0.05) and reading unlined books (p-value (0.043)) <α ( 0.05).